Grupo mediano de personas en una reunión. (UNED, 2023)
Aparecen de derecha a izquierda Enrique Góngora Trejos, Chester Zelaya Goodman - Rector, Álvaro Avilés Vargas, Marco Vinicio Álvarez, Jorge Enrique Álvarez, Sherman Thómas Jackson, Helena Ramírez Valverde, Luis Garita